2019
DOI: 10.29313/jiff.v2i1.4230
|View full text |Cite
|
Sign up to set email alerts
|

POTENSI AKTIVITAS ANTIBAKTERI DARI FRAKSI ETIL ASETAT DAUN JAMBU AIR [Eugenia aqueum (Burn F.) Alston] TERHADAP STHAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI

Abstract: Staphylococcus aureus (S. Aureus) adalah termasuk penyusun flora normal jenis Gram positif. Tetapi apabila jumlahnya berlebih akan menjadi patogen pada manusia. Begitu pula dengan Escherichia coli (E. coli) yang merupakan bakteri gram negatif Antibakteri yang tersedia umumnya memiliki spektrum luas sehingga efek sampingnya dapat merusak flora normal bila digunakan jangka panjang. Flavonoid senyawa fenolik dan tannin dimungkinkan berkhasiat antibakteri. Sediaan uji berupa seri konsentrasi fraksi etil asetat dau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Page 226 SIRES to decline. This showed that the working type of water fraction is primary bactericide [14].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Page 226 SIRES to decline. This showed that the working type of water fraction is primary bactericide [14].…”
Section: Resultsmentioning
confidence: 94%
“…Based on Bell's criteria, the water fraction showed strong antibacterial activity because it produced an inhibitory diameter of > 6 mm [13]. The water fraction showed a broad working spectrum because it was active in both Gram positive and negative bacteria [14]. The water fraction has a bactericide working type in both S. aureus and E. coli.…”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial activity can be aimed at the presence of positive results on phytochemical tests on flavonoid compounds, alkaloids, tannins, saponins and terpenoids. 10 Choesrina conducted an antibacterial test of guava leaf extract against the growth of Sthaphylococcus aureus and Escherichia coli bacteria, in the study it can be concluded that there is antibacterial activity. When compared to the use of chlorhexidine, guava leaf extract is safer than long-term use of chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%